2020
DOI: 10.1051/0004-6361/201937394
|View full text |Cite
|
Sign up to set email alerts
|

A transition between the hot and the ultra-hot Jupiter atmospheres

Abstract: A key hypothesis in the field of exoplanet atmospheres is the trend of atmospheric thermal structure with planetary equilibrium temperature. We explore this trend and report here the first statistical detection of a transition in the near-infrared atmospheric emission between hot and ultra-hot Jupiters. We measure this transition using secondary eclipse observations and interpret this phenomenon as changes in atmospheric properties, and more specifically in terms of transition from non-inverted to inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 114 publications
7
97
0
Order By: Relevance
“…Most ultrahot Jupiters with observed secondary eclipse spectra show a temperature inversion (e.g., Christiansen et al 2010;Haynes et al 2015;Evans et al 2017;Sheppard et al 2017;Kreidberg et al 2018), generally between 10 and 100 mbar, most often identified by a positive deviation of the 4.5 μm flux from a blackbody. Baxter et al (2020) have empirically found that this transition between highly irradiated gas giants with and without thermal inversions likely occurs at 1660±100 K, well below the temperature of LTT 9779b. To occur, these inversions generally require higher opacities in the optical than in the infrared, believed to be caused by the presence of optical absorbers such as TiO and VO (Hubeny et al 2003).…”
Section: Discussion and Future Prospectsmentioning
confidence: 91%
See 1 more Smart Citation
“…Most ultrahot Jupiters with observed secondary eclipse spectra show a temperature inversion (e.g., Christiansen et al 2010;Haynes et al 2015;Evans et al 2017;Sheppard et al 2017;Kreidberg et al 2018), generally between 10 and 100 mbar, most often identified by a positive deviation of the 4.5 μm flux from a blackbody. Baxter et al (2020) have empirically found that this transition between highly irradiated gas giants with and without thermal inversions likely occurs at 1660±100 K, well below the temperature of LTT 9779b. To occur, these inversions generally require higher opacities in the optical than in the infrared, believed to be caused by the presence of optical absorbers such as TiO and VO (Hubeny et al 2003).…”
Section: Discussion and Future Prospectsmentioning
confidence: 91%
“…For example, hot Jupiters with T eq 2200 K are consistent with zero Bond albedo and inefficient global heat redistribution, indicating bright, hot daysides and relatively cold, dark nightsides (Garhart et al 2020). Furthermore, hot Jupiters with T eq 1900 K have consistent dayside brightness temperatures in the 3.6μm and 4.5μm Spitzer InfraRed Array Camera (IRAC) bandpasses (Garhart et al 2020;Baxter et al 2020). In addition, the hottest planets, such as the so-called "ultrahot Jupiters," also show qualitatively different atmospheres in which opacity from H − , hydrides, and other nonoxides begin to play a much larger role than in the (relatively) cooler population (Arcangeli et al 2018;Lothringer et al 2018;Mikal-Evans et al 2019).…”
Section: Introductionmentioning
confidence: 95%
“…We note that a recent study by Baxter et al (2020) was unable to reproduce this trend in their compilation of Spitzer secondary eclipse data when using a PHOENIX stellar model and integrating across the Spitzer bandpass (although when using a blackbody as in Schwartz & Cowan (2015), they were able to retrieve the trend). However, this study used the observed brightness temperature at 3.6 µm as opposed to the error weighted average of the brightness temperatures in the 3.6 and 4.5 µm bandpasses (C. Baxter, email communication).…”
Section: Trends As a Function Of Incident Fluxmentioning
confidence: 80%
“…Garhart et al (2020) found evidence for such a correlation in their study, but concluded that the trends they saw were not well-matched by commonly used model atmosphere grids. Baxter et al (2020) used an expanded Spitzer data set to reproduce the trend found by Garhart et al (2020) and concluded that models including temperature inversions were better able to capture the qualitative shifts in spectral shape as a function of temperature. As shown in the left-hand panel of Figure 5, we also find that the most highly irradiated planets tend to lie above the line (meaning their 4.5 µm brightness temperature is higher than their 3.6 µm brightness temperature).…”
Section: Trends As a Function Of Incident Fluxmentioning
confidence: 99%
See 1 more Smart Citation